PENGARUH KOMUNIKASI ORGANISASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PASAR SWALAYAN MAJU BERSAMA MEDAN - Elvie Maria; Edison Edison; Wandry Wandry (Jurnal Ilmu Manajemen METHONOMIX, 2021)
This study aims to determine and analyze the effect of organizational communication, work motivation, and work environment on employee performance. The population in this study were all employees of PT. The Maju Bersama Supermarket in Medan (PSMBM) with a total of 173 and a sample of 121 people using the Slovin formula. The research method used is the quantitative descriptive research method and the variables of this research are organizational communication, work motivation, work environment, and employee performance. The results showed that organizational communication, work motivation, and work environment have a strong and positive influence on employee performance with a contribution of 71.5%. And explained that organizational communication, work motivation, and work environment simultaneously had links and real impact on the employee performance.